Utilization of Modified Zeolite as Catalyst for Steam Gasification of Palm Kernel Shell - Joko Waluyo; Petric Marc Ruya; Dwi Hantoko; Jenny Rizkiana; I.G.B.N. Makertihartha; Mi Yan; Herri Susanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Syngas from biomass gasification is being developed for alternative feedstock in the chemical industry. Palm kernel shell which is generated from palm oil industry can be potentially used as raw material for gasification process. The purpose of this study was to investigate the use of modified natural zeolite catalysts in steam gasification of palm kernel shells. Mordenite type zeolite was modified by acid leaching to be used as a tar cracking catalyst. Steam gasification was conducted at the temperature range of 750–850 °C and the steam to biomass ratio was in the range of 0–2.25. The result showed that steam gasification of palm kernel shell with the addition of zeolite catalyst at 750 °C and steam to biomass ratio 2.25 could reduce tar content up to 98% or became 0.7 g/Nm3. In this study, gasification of palm kernel shells produced syngas with the hydrogen concentration in the range of 52–64% and H2/CO ratio of 2.7–5.7. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).